VD_FINDINFO Décision / 2014 / 730 vom 8. Juli 2014 - VD Tribunal cantonal (2014)
NON-LIEU, VIOLATION DE DOMICILE, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, EXEMPTION DE PEINE | 53 CP, 310 CPP (CH), 8 CPP (CH)